Prevalence of genital Chlamydia trachomatis infection in the general population of Slovenia: serious gaps in control. Issue 2 (30th March 2004) - Klavs, I; Rodrigues, L C; Wellings, K; Keše, D; Hayes, R
Abstract : Objectives: One of the objectives of the first national survey of sexual lifestyles, attitudes, and health in Slovenia was to estimate the prevalence of and risk factors for genital Chlamydia trachomatis infection in Slovenian adults aged 18–49 years. Methods: Data were collected over 1999–2001 from a probability sample of the general population by face to face interviews and anonymous self administered questionnaires. Respondents were invited to provide a first void urine (FVU) specimen for polymerase chain reaction testing for C trachomatis infection. We compared the results to the equivalent British survey. Results: 1447 individuals contributed FVU specimens (82.6% of survey respondents, 55.3% of those eligible). C trachomatis infection was diagnosed in 3.0% of men and 1.6% of women. Prevalence was highest in men and women aged 18–24 years (4.1% for both). Individuals reporting first heterosexual intercourse before the age of 16, unprotected sexual intercourse with at least one heterosexual partner during the preceding year, concurrent heterosexual relationships during the preceding year, and five or more lifetime heterosexual partners had a higher prevalence. The association was statistically significant only for five or more lifetime partners (adjusted OR 3.0; 95% CI 1.3 to 6.9; p = 0.01). Conclusions: A relatively high prevalence of genital C trachomatis infection among 18–24 year old Slovenians, in the presence of relatively low risk sexual behaviour and low reported incidence rates of chlamydia infection, suggest serious gaps in the diagnosis and treatment of the condition. The results provide support for the introduction of chlamydia screening in Slovenia.